2003
DOI: 10.1002/ajmg.a.20422
|View full text |Cite
|
Sign up to set email alerts
|

Specific clinical and brain MRI features in mentally retarded patients with mutations in the Oligophrenin‐1 gene

Abstract: Oligophrenin-1 (OPHN-1) gene disruption is known as responsible for so called "non-specific" X-linked mental retardation (MR) Billuart et al. [1998: Nature 392:923-926]. In order to search for a possible specific clinical and radiological profile for mutation in the OPHN-1 gene, clinical and 3D brain MRI studies were performed in the two families with a known mutation in OPHN-1 reported so far: a 19-year-old female with an X;12 balanced translocation encompassing OPHN-1, and four affected males of family MRX60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 26 publications
5
36
1
2
Order By: Relevance
“…OPHN1 mutations in humans lead to MR associated with cerebellum hypoplasia and variable dilatation of the lateral ventricles (Bergmann et al, 2003;Philip et al, 2003;des Portes et al, 2004;Zanni et al, 2005). We found that loss of ophn1 function in mice recapitulates some of the human phenotypes, such as behavioral, social, and cognitive impairments, as well as the dilatation of the cerebral ventricles.…”
Section: Discussionmentioning
confidence: 69%
“…OPHN1 mutations in humans lead to MR associated with cerebellum hypoplasia and variable dilatation of the lateral ventricles (Bergmann et al, 2003;Philip et al, 2003;des Portes et al, 2004;Zanni et al, 2005). We found that loss of ophn1 function in mice recapitulates some of the human phenotypes, such as behavioral, social, and cognitive impairments, as well as the dilatation of the cerebral ventricles.…”
Section: Discussionmentioning
confidence: 69%
“…Billuart et al (1998) also identified a frameshift mutation in a pedigree with 4 affected males (MRX60) that resulted in the production of a truncated protein. Des Portes et al (2004) carefully investigated the brain structure of these patients and described a specific dysgenesis of the cerebellar vermis and some diffuse cortico-subcortical atrophy. Thirteen more pedigrees with mutations in OPHN1 have been reported since 1998 (Tentler et al, 1999;Bergmann et al, 2003;Philip et al, 2003;Chabrol et al, 2005;Zanni et al, 2005;Menten et al, 2007;Froyen et al, 2007;Madrigal et al, 2008;Al Owain et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Patient III-4 presented with triventricular hydrocephalus as an infant and required ventriculoperitoneal shunting. des Portes et al (2004) reported cortico-subcortical atrophy and correlated it with the severity of mental retardation. We also observed ventricular enlargement and cortico-subcortical atrophy but only in patient II-8 ( Figure 2C) who is the oldest but also the least affected, suggesting that such degenerative changes may be age-related and not correlated with intellectual functioning.…”
Section: Discussionmentioning
confidence: 99%
“…L'examen rétrospectif des patients a permis de définir des signes dysmorphiques et de caractériser par IRM une hypoplasie du cervelet, avec une agénésie des lobules VI et VII au niveau du vermis postérieur (Figure 3) [18][19][20]. En corollaire, une étude prospective récente, réalisée chez des patients atteints de RM avec hypoplasie cérébelleuse, montre que 12 % d'entre eux présentent une mutation dans le gène OPHN1 [21].…”
Section: Mutations Du Gène De L'oligophrénine 1 : De Rmx à Rmxsunclassified